2006
DOI: 10.1111/j.1537-2995.2006.01043.x
|View full text |Cite
|
Sign up to set email alerts
|

New mutation in the platelet β3‐integrin gene: implication for the diagnosis of fetomaternal alloimmunization

Abstract: Even if such mutations are a rare event, PLT phenotyping is still of interest to avoid rare false PLT typing assignation, the unknown polymorphism being only discovered by such a combination of techniques.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
15
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(15 citation statements)
references
References 15 publications
0
15
0
Order By: Relevance
“…Although genotyping is widely used, unknown genetic variants may alter the results. Investigations for NAIT cases have revealed that silent mutations may induce a false HPA typing and therefore false diagnosis [25]. A discrepancy between genotyping and phenotyping led to find this mutation ( Fig.…”
Section: Genotypingmentioning
confidence: 99%
“…Although genotyping is widely used, unknown genetic variants may alter the results. Investigations for NAIT cases have revealed that silent mutations may induce a false HPA typing and therefore false diagnosis [25]. A discrepancy between genotyping and phenotyping led to find this mutation ( Fig.…”
Section: Genotypingmentioning
confidence: 99%
“…Although anti-Jk b is a well-recognized cause of severe acute or delayed hemolytic transfusion reactions, anti-Jk b is rarely associated with severe hemolytic disease of the fetus or newborn (HDFN). [1][2][3][4] The reason why anti-Jk b rarely causes HDFN, even when present in a relatively high titer, is unclear. 5 We would like to share with readers 402 TRANSFUSION Volume 48, February 2008…”
Section: Severe Hemolytic Disease Of the Fetus Due To Anti-jk Bmentioning
confidence: 99%
“…We recently described a new mutation in the b3-integrin gene in a pregnant woman, which induced a false-negative HPA-1a typing and, consequently, a false diagnosis. 2 A discrepancy between genotyping and phenotyping for HPA-1 led us to find a 262T>C silent mutation located under the antisense primer we use for PCR-SSP. This mutation, which does not change the amino acid sequence, prevents HPA-1a allele DNA amplification.…”
mentioning
confidence: 99%
“…Polymerase chain reaction–sequence specific primers (PCR‐SSP) and PCR‐restriction fragment length polymorphism analysis are commonly in use for platelet genotyping. However, a recent publication has shown that silent mutation localized in the PCR primers might lead to discrepancies observed between these two techniques and a false diagnosis might follow [15]. Therefore, in the current workshop DNA with mutations altering the PCR‐SSP technique have been included in order to evaluate the local genotyping method.…”
Section: Platelet Genotypingmentioning
confidence: 99%